PENGARUH CORPORATE GOVERNANCE TERHADAP INTEGRITAS LAPORAN KEUANGAN - Ela Widasari; Nunayati Nunayati (The Asia Pacific Journal Of Management Studies, 2021)
This research was conducted with the aim of knowing that Corporate Governance can affect the Integrity of Financial Statements in Property, Real Estate and Building Construction Service Companies listed on the Indonesia Stock Exchange (IDX). The method used in this research is a quantitative research method. The population used is all Property, Real Estate and Building Construction Service Companies listed on the Indonesia Stock Exchange (IDX) using a purposive sampling method. Collection of data obtained through secondary data. The data analysis technique used in this study is the Classical Assumption Test which consists of (Normality Test, Heteroscedasticity Test, Multicollinearity Test and Autocorrelation Test), Multiple Linear Regression Analysis Test, Correlation Analysis Test, Coefficient of Determination Test, and Hypothesis Test which consists of ( Statistical Test t and Statistical Test F). The test results show that the coefficient of determination is 19.6%, meaning that the variable Integrity of Financial Statements can be explained by independent variables consisting of Corporate Governance (Institutional Ownership, Managerial Ownership and Audit Committee) of 19.6%. Then the results of statistical testing t shows that Institutional Ownership Thus Institutional Ownership (X1) has no partial effect on the Integrity of Financial Statements. Managerial Ownership (X2), so that Managerial Ownership does not partially affect the Integrity of Financial Statements. Audit Committee, so that the Audit Committee has a partial effect on Report Integrity. And the test results are based on the F statistical test in the study. Thus Corporate Governance (Institutional Ownership, Managerial Ownership and Audit Committee) influence simultaneously or simultaneously on the Integrity of Financial Statements.